Nanostructured lipid carriers loaded with tributyrin as an alternative to improve anticancer activity of all-trans retinoic acid. Issue 2 (February 2014) - Silva, Elton Luiz; Carneiro, Guilherme; Caetano, Priscila Albuquerque; Goulart, Gisele; Ferreira Costa, Daniel; de Souza-Fagundes, Elaine Maria; Gomes, Dawidson Assis; Ferreira, Lucas Antônio Miranda
<x xml:space="preserve">Abstract</x> Objectives: All-trans retinoic acid (ATRA) is one of the most successful examples of differentiation agents and histone deacetylase inhibitors, such as tributyrin (TB), are known for their antitumor activity and potentiating action of drugs, such as ATRA. Nanostructured lipid carriers (NLC) represent a promising alternative to the encapsulation of lipophilic drugs such as ATRA. This study aims to develop, characterize and evaluate the cytotoxicity of ATRA–TB-loaded NLC for cancer treatment. Methods: The influence of in situ formation of an ion pairing between ATRA and a lipophilic amine (benethamine) on the characteristics of NLC (size, zeta potential, encapsulation efficiency) was evaluated. TB, a butyric acid donor, was used as a component of the lipid matrix. In vitro activity on cell viability and distribution of cell cycle phases were evaluated for MCF-7, MDA-MB-231, HL-60 and Jurkat cell lines. Results: The presence of the amine significantly increased the encapsulation efficiency of ATRA in NLC. Inhibition of cell viability by TB–ATRA-loaded NLC was more pronounced than the free drug. Analysis of the distribution of cell cycle phases also showed increased activity for TB–ATRA-loaded NLC, with the clear effect of cell cycle arrest in G0/G1 phase transition. The presence of TB played an important role in the activity of the formulation. Conclusion: Taken together, these findings suggest that TB–ATRA-loaded NLC represents a promising alternative to intravenous administration of ATRA in cancer treatment.